Characterisation of specified granular fill materials for radon mitigation by soil depressurisation systems. (10th July 2018) - Hung, Le Chi; Goggins, Jamie; Fuente, Marta; Foley, Mark
Highlights: A test apparatus was developed to measure air permeability of granular materials. Air permeability is strongly influenced by the compaction and the change of moisture. Poorly-graded granular material extracts air much better than well-graded granular material. Empirical equations have been proposed. Abstract: A series of experimental laboratory tests were conducted to quantitatively investigate the characterisation of the T1 Struc and T2 Perm specified granular fill materials for soil depressurisation systems for radon reduction under buildings. The characterisation included determination of grading curves, measurement of air permeability, porosity, and the effective particle diameter of the stone. A test apparatus was developed to measure the air permeability of the granular fill materials under different compaction degrees. Test results showed that the T1 Struc and T2 Perm specified granular fill materials could be classified as well-graded and poorly-graded granular materials, respectively. The air permeability and porosity of T1 Struc decrease with the increase in compaction degree and are strongly affected by the change of moisture content. However, the air permeability of T2 Perm was found to be independent of the compaction degree and variation of moisture content. Computational Fluid Dynamic (CFD) simulations were validated to simulate the flow behaviour of the T1 Struc and T2 Perm granular fill materials. The primary parameters for simulating the flow behaviour of the materials were confirmed to be the air permeability, porosity, and effective particle diameter. Based on the CFD simulation results, the effective particle diameter was found to vary with the compaction degree for T1 Struc, whereas that of T2 Perm was constant at 16.2 mm.